Ceramic-copper composite and method for producing ceramic-copper composite
By forming Cu-rich phases in the brazing material layer of ceramic-copper composites and optimizing bonding conditions, the heat cycle characteristics of the composites are significantly improved, addressing the limitations of existing technologies.
Patent Information
- Application Number
- JP2021572809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-23
- Filing Date
- 2021-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-22
AI Technical Summary
The existing ceramic-copper composites, as described in Patent Document 1, have room for improvement in terms of heat cycle characteristics.
The formation of a plurality of Cu-rich phases in the brazing material layer, which are convex towards the copper layer side, improves the heat cycle characteristics of the ceramic-copper composite. This is achieved by selecting appropriate bonding conditions, such as rapid heating and cooling under a nitrogen atmosphere, and setting the heating peak temperature high.
The ceramic-copper composite exhibits excellent heat cycle characteristics, with improved peel strength at the interface between the brazing material layer and the copper layer, leading to enhanced reliability and performance in thermal cycling tests.
Smart Images

Figure 0007662539000002 
Figure 0007662539000003 
Figure 0007662539000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a ceramic-copper composite and a method for producing a ceramic-copper composite. [Background technology]
[0002] Various developments have been made on ceramic-copper composites. One such technique is described in Patent Document 1. Patent Document 1 describes a method for producing a ceramic circuit board, in which a Cu plate is pressed against both the front and back surfaces of an aluminum nitride substrate on which a brazing paste has been printed, and then heat treated for 15 minutes at 800°C in a vacuum atmosphere (see paragraph 0034 of Patent Document 1, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-101415 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, as a result of investigations conducted by the present inventors, it was found that the ceramic-copper composite described in Patent Document 1 leaves room for improvement in terms of heat cycle characteristics. [Means for solving the problem]
[0005] As a result of further investigation, the inventors discovered that the heat cycle characteristics of the ceramic-copper composite can be improved by forming multiple Cu-rich phases in the region of the brazing material layer that is convex toward the copper layer, and thus completed the present invention.
[0006] According to the present invention, A ceramic layer, a copper layer, and a brazing material layer interposed between the ceramic layer and the copper layer and containing Ag and Sn or In; A flat ceramic-copper composite comprising: The ceramic-copper composite is provided in such a way that, when the ceramic-copper composite is cut in a plane perpendicular to its main surface, at least one of the cut surfaces has an uneven portion formed on the copper layer side of the brazing material layer, and a plurality of Cu-rich phases are present in a state spaced apart from each other within at least one of the convex portions.
[0007] Further, according to the present invention, A step of preparing a flat laminate in which a ceramic layer, a brazing material containing Ag, and a copper layer are laminated; A bonding step of heating the laminate at a temperature of 750° C. or more and 900° C. or less in a nitrogen atmosphere after increasing the temperature at a rate of 20° C. / min or more and 150° C. / min or less, The present invention provides a method for producing a flat ceramic-copper composite comprising the ceramic layer, the copper layer, and a brazing material layer containing Ag and interposed between the ceramic layer and the copper layer. Effect of the Invention
[0008] According to the present invention, there are provided a ceramic-copper composite having excellent heat cycle characteristics, and a method for producing the same. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a cross-sectional view of a joint in an outer portion of an example of a ceramic-copper composite according to the present embodiment. [Diagram 2] FIG. 2 is an enlarged view of the α region of FIG. [Diagram 3] FIG. 3 is an enlarged view of the β region of FIG. [Figure 4] 1 is an SEM image of the ceramic-copper composite of Example 1. [Diagram 5] 1 is an SEM image of the ceramic-copper composite of Example 1. [Figure 6]FIG. 2 is a binarized SEM image of the ceramic-copper composite of Example 1. [Figure 7] 1 is an SEM image of the ceramic-copper composite of Example 2. [Figure 8] 1 is an SEM image of the ceramic-copper composite of Example 2. [Figure 9] FIG. 2 is a binarized SEM image of the ceramic-copper composite of Example 2. [Figure 10] 1 is a SEM image of the ceramic-copper composite of Example 3. [Figure 11] 1 is a SEM image of the ceramic-copper composite of Example 3. [Figure 12] FIG. 1 is a binarized SEM image of the ceramic-copper composite of Example 3. [Figure 13] 1 is an SEM image of the ceramic-copper composite of Example 4. [Figure 14] 1 is an SEM image of the ceramic-copper composite of Example 4. [Figure 15] FIG. 1 is a binarized SEM image of the ceramic-copper composite of Example 4. [Figure 16] 1 is an SEM image of the ceramic-copper composite of Example 5. [Figure 17] 1 is an SEM image of the ceramic-copper composite of Example 5. [Figure 18] FIG. 13 is a binarized SEM image of the ceramic-copper composite of Example 5. [Figure 19] 1 is an SEM image of the ceramic-copper composite of Comparative Example 1. [Figure 20] 1 is an SEM image of the ceramic-copper composite of Comparative Example 1. [Figure 21] FIG. 2 is a binarized view of an SEM image of the ceramic-copper composite of Comparative Example 1. [Figure 22] 1 is an SEM image of the ceramic-copper composite of Comparative Example 2. [Diagram 23] 1 is an SEM image of the ceramic-copper composite of Comparative Example 2. [Figure 24] FIG. 2 is a binarized view of an SEM image of the ceramic-copper composite of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference numerals and their explanations will be omitted as appropriate. Also, the drawings are schematic diagrams and do not correspond to the actual dimensional ratios. In the present embodiment, the directions of front, back, left, right, top and bottom are defined as shown in the drawings. However, this is defined for the sake of convenience in order to easily explain the relative relationships of the components. Therefore, it does not limit the directions during the manufacture or use of the product embodying the present invention.
[0011] The ceramic-copper composite of this embodiment will be outlined below.
[0012] The ceramic-copper composite is a flat plate-like member including a ceramic layer, a copper layer, and a brazing material layer containing Ag and Sn or In and interposed between the ceramic layer and the copper layer. When the ceramic-copper composite is cut in a plane perpendicular to its main surface, at least one of the cut surfaces has an uneven portion formed on the copper layer side of the brazing material layer, and multiple Cu-rich phases are present in a spaced-apart relationship within at least one of the convex portions.
[0013] According to the findings of the present inventors, it has been found that the heat cycle characteristics of a ceramic-copper composite can be improved by forming multiple Cu-rich phases in the region of the brazing material layer that is convex toward the copper layer.
[0014] Although the detailed mechanism is unclear, it is believed that the presence of multiple Cu-rich phases in the convex portion improves the peel strength at the interface between the brazing material layer and the copper layer, thereby suppressing the occurrence of peeling between them after a heat cycle test, thereby improving the heat cycle characteristics.
[0015] In addition, such a structure can be obtained by appropriately selecting the joining conditions of the ceramic-copper composite, such as adopting rapid heating and rapid cooling conditions under a nitrogen atmosphere and setting a high heating peak temperature. Although the detailed mechanism is unclear, it is speculated that the interface of the Ag-rich phase in the brazing material layer moves toward the inside of the copper layer, forming a convex Ag-rich phase, and inside the convex parts made of the Ag-rich phase, Cu atoms diffused from the copper layer or Cu atoms contained in the brazing material form multiple Cu-rich phases.
[0016] By forming a circuit pattern on a copper layer using the ceramic-copper composite of this embodiment, a ceramic circuit board having a copper heat sink plate and a copper circuit plate on both sides of the ceramic layer via a brazing material layer can be realized. Such a ceramic circuit board can improve heat cycle characteristics.
[0017] By using such a ceramic circuit board, it is possible to realize an electronic component module including the ceramic circuit board, electronic components provided on the copper circuit plate of the ceramic circuit board, and a heat sink provided on the copper heat sink of the ceramic circuit board. By using the above-mentioned ceramic circuit board, it is possible to improve the connection reliability of the electronic component module.
[0018] The ceramic-copper composite 100 can be used in a variety of applications, one of which is as an in-vehicle power module that requires strict reliability.
[0019] The ceramic-copper composite of this embodiment will be described in detail below.
[0020] Fig. 1 is a cross-sectional view of a joint in an outer portion of an example of a ceramic-copper composite 100, Fig. 2 is an enlarged view of the α region in Fig. 1, and Fig. 3 is an enlarged view of the β region in Fig. 2. In Fig. 1, black indicates a ceramic layer 1, gray indicates a copper layer 2, and white indicates a brazing material layer 3. In Fig. 3, in the brazing material layer 3, white indicates an Ag-rich phase 5 and gray indicates a Cu-rich phase 4.
[0021] A ceramic-copper composite 100 shown in FIG. 1 has a structure in which a ceramic layer 1, a brazing material layer 3, and a copper layer 2 are laminated in this order.
[0022] For example, nitride ceramics such as silicon nitride and aluminum nitride, oxide ceramics such as aluminum oxide and zirconium oxide, carbide ceramics such as silicon carbide, boride ceramics such as lanthanum boride, etc. can be used as the ceramic layer 1. Among these, non-oxide ceramics such as aluminum nitride and silicon nitride are preferred from the viewpoint of metal bonding properties, and silicon nitride is more preferred from the viewpoint of excellent mechanical strength and fracture toughness.
[0023] The thickness of the ceramic layer 1 is not particularly limited, but is generally about 0.1 mm to 3.0 mm. In particular, taking into consideration heat dissipation characteristics and reduced thermal resistivity, the thickness is preferably 0.2 mm to 1.2 mm, and more preferably 0.25 mm to 1.0 mm. In this specification, the symbol "to" indicates that the upper and lower limits are included, unless otherwise specified.
[0024] The copper layer 2 is not particularly limited, and can be formed of, for example, a copper plate. The material used for the copper plate is preferably pure copper. The thickness of the copper plate is not particularly limited, but is generally 0.1 mm to 1.5 mm, and from the viewpoint of heat dissipation, it is preferably 0.3 mm or more, and more preferably 0.5 mm or more.
[0025] A method for forming a circuit pattern on the copper layer 2 may be, for example, a method in which a metal plate (e.g., a copper plate) is bonded to the ceramic layer 1 using a brazing material layer 3, and then an etching mask is formed and an etching process is performed.
[0026] The brazing material layer 3 is made of a brazing material containing Ag and Sn or In. The brazing material may be configured to contain at least any one of Ag and Sn, Ag and In, or Ag, Sn and In. The brazing material may contain other elements in addition to these elements, such as Cu, Ti, etc.
[0027] At least one of the cut surfaces (FIGS. 1 to 3) of the ceramic-copper composite 100 cut along a plane perpendicular to its main surface has an uneven portion on the copper layer 2 side of the brazing material layer 3. In at least one protrusion 6 of the uneven portion, a plurality of Cu-rich phases 4 are configured to be present and spaced apart from each other.
[0028] The cut sections in FIGS. 1 to 3 show the outside of the ceramic-copper composite 100, that is, the area near the end.
[0029] The protruding portion 6 of the brazing material layer 3 may be defined as, for example, a portion that exceeds a position of 1 / 2 of the average thickness of the brazing material layer 3 in a vertical direction from the interface between the ceramic layer 1 and the brazing material layer 3 toward the copper layer 2 in a cross-sectional view. Also, the concave portion of the uneven portion of the brazing material layer 3 may be defined as a portion that does not exceed a position of 1 / 2 of the average thickness of the brazing material layer 3. Here, the average thickness of the brazing material layer 3 may be measured by image observation as described below, from the interface between the ceramic layer 1 and the brazing material layer 3 to the interface between the brazing material layer 3 and the copper layer 2, and the average value of the maximum and minimum thicknesses may be used.
[0030] In this embodiment, image observation may be performed as follows. Using a scanning electron microscope, obtain an SEM image at any position on the joint interface of the cross section of the ceramic-copper composite. Using the obtained SEM image, observe three arbitrary fields of view of a 40 μm × 60 μm area near the center of the plate thickness cross section in the center of the longitudinal direction. Regarding the value calculated based on the observation field, the average value obtained by averaging the values measured by observing three fields may be used.
[0031] By observing the image as described above, the length of the observation field in the sheet width direction and the length of the line segment at the interface between the brazing material layer 3 and the copper layer 2 are obtained, and these are designated as L1 and L2, respectively, as shown in FIG. In this case, the ratio of L1 to L2 (L2 / L1) may be, for example, 1.25 to 5.0, more preferably 1.30 to 3.0. By setting L2 / L1 to the above lower limit or more, it is presumed that the interfacial bonding between the brazing material layer 3 and the copper layer 2 is improved, and therefore the heat cycle characteristics can be improved.
[0032] The brazing material layer 3 may have a plurality of protrusions 6 penetrating into the copper layer 2. The plurality of protrusions 6 may be formed at least near the ends of the ceramic-copper composite 100, and may be formed both near the ends and inside. Furthermore, the number of protrusions 6 of the brazing material layer 3 is not particularly limited, but may be configured so that there are more protrusions 6 in the outer region near the end than in the inner region. This makes it possible to prevent peeling, cracks, and the like from occurring near the outer periphery during a heat cycle test when the ceramic-copper composite 100 is viewed in a direction perpendicular to the main surface.
[0033] The Cu-rich phase 4 present in the protruding portion 6 of the brazing material layer 3 may be configured in various shapes such as substantially spherical or substantially elliptical in cross section, and at least one of them may be formed in a streak-like shape. These may be used alone or in combination of two or more. In addition, a plurality of streak-like Cu-rich phases 4 may be present in the same protruding portion 6, and may be arranged apart from each other to form a streak pattern.
[0034] The aspect ratio of one of the streaky Cu-rich phases 4 may be, for example, more than 1 and not more than 10, and preferably not less than 2 and not more than 9. This can improve the repeat cycle characteristics.
[0035] The number density of the Cu-rich phase 4 in the protrusion 6 of the brazing material layer 3 is, for example, 0.1 / μm 2 More than 20 pieces / μm 2 Less than or equal to 0.2 particles / μm 2 More than 10 pieces / μm 2By making the number density of the Cu-rich phase 4 equal to or greater than the above lower limit, the heat cycle characteristics can be improved.
[0036] The number density of the Cu-rich phase 4 was calculated by binarizing the SEM image used in the above image observation using the image analysis software GIMP2 (threshold value 90), measuring the area of the brazing material layer 3 using the image analysis software Image-pro plus, and calculating the number density of the Cu-rich phase 4 (pieces / μm 2 ) is required. Formula: [Number density of Cu-rich phase 4]=[Number of Cu-rich phase 4] / [Area of brazing material layer 3]
[0037] The Cu-rich phase in the brazing material layer 3 may include, for example, a fine phase having a size of 0.3 μm or more and less than 1.0 μm, and a coarse phase having a size of 1.0 μm or more and 7.5 μm or less. The presence of the fine phase and the coarse phase allows the Cu-rich phase 4 to be present in the protrusions 6, and the number density of the Cu-rich phase 4 in the protrusions 6 can be increased.
[0038] The brazing material layer 3 is only required to be configured so as to have a plurality of Cu-rich phases 4 at least in the protrusions 6, and may or may not have the Cu-rich phases 4 in regions other than the protrusions 6.
[0039] The brazing material layer 3 is composed of an Ag-rich phase 5. The Ag-rich phase 5 may be continuously formed in the protruding portion 6 of the brazing material layer 3. In the Ag-rich phase 5 present in the protruding portion 6, a plurality of Cu-rich phases 4 may be discontinuously scattered.
[0040] The Ag-rich phase 5 may be formed at least partially or continuously in the outer edge of the protrusion 6, i.e., in the portion of the protrusion 6 in contact with the interface between the brazing material layer 3 and the copper layer 2. In other words, the protrusion 6 may be configured such that the Cu-rich phase 4 is present discretely inside the region surrounded by the Ag-rich phase 5.
[0041] The term "Cu-rich" in the Cu-rich phase 4 may be defined as including mainly a Cu solid solution. The abundance ratio of Cu in the Cu-rich phase 4 of the protrusions 6 may be, for example, 80 mass % or more. The term "Ag-rich" in the Ag-rich phase 5 may be defined as including mainly an Ag solid solution. The abundance ratio of Ag in the Ag-rich phase 5 of the protrusions 6 may be, for example, 80 mass % or more. The Cu and Ag contents are quantitatively analyzed using an electron beam excited X-ray analyzer (EPMA).
[0042] The diffusion distance of Ag, which is a component of the brazing material layer 3, is, for example, 10 μm to 50 μm, or preferably 15 μm to 45 μm.
[0043] Here, the diffusion distance of Ag can be defined as the distance from the surface of the ceramic layer 1 to the part where Ag has diffused the furthest from the surface of the ceramic layer 1 toward the surface of the copper layer 2 (the direction perpendicular to the main surface of the ceramic-copper composite 100). The diffusion distance of Ag does not necessarily coincide with the thickness of the continuous brazing material layer. The diffusion distance of Ag was determined by observing three randomly selected non-overlapping areas (a range of 250 μm in the horizontal direction of the joint interface) at a magnification of 500x using a scanning electron microscope from the cross section of the ceramic-copper composite 100 (cross section through the plate thickness at the center of the longitudinal direction), and the diffusion distance of Ag was determined as the maximum of the diffusion distances of Ag measured in each field of view.
[0044] Furthermore, the ceramic-copper composite 100 may have a bonding layer interposed between the ceramic layer 1 and the brazing material layer 3, the bonding layer including Ti. The joint void ratio of such a ceramic-copper composite 100 may be set to, for example, 1.0% or less, which can prevent the copper plate from peeling off during thermal cycles.
[0045] Furthermore, the brazing material layer 3 may be configured so as not to have a part of the brazing material layer 3 that creeps up the side surface of the copper layer 2 .
[0046] Next, a method for producing the ceramic-copper composite 100 will be described.
[0047] One method for manufacturing the ceramic-copper composite 100 includes a step of preparing a flat laminate in which a ceramic layer, a brazing material containing Ag, and a copper layer are laminated, and a step of joining the laminate. This results in a flat ceramic-copper composite 100 including a ceramic layer 1, a copper layer 2, and a brazing material layer 3 containing Ag that is interposed between the ceramic layer 1 and the brazing material layer 3.
[0048] The brazing filler metal composition, Ag / Cu ratio, is increased from 72 mass%:28 mass% which is the eutectic composition of Ag and Cu, to prevent the Cu-rich phase from coarsening and form a brazing filler metal layer structure with a continuous Ag-rich phase. If the amount of Ag powder is large and the amount of Cu powder is small, the Ag powder will not melt completely during bonding and will remain as a bonding void. Furthermore, Sn or In contained in the brazing filler metal powder is a component that reduces the contact angle of the brazing filler metal with the ceramic substrate and improves the wettability of the brazing filler metal. If the amount is too small, the wettability with the ceramic substrate will decrease, which may lead to poor bonding. If the amount is too large, the Ag-rich phase in the brazing filler metal layer will become discontinuous due to the Cu-rich phase, which may become the starting point for cracking the brazing filler metal, which may reduce the thermal cycle characteristics of the ceramic circuit board. Therefore, the compounding ratio of Ag powder, Cu powder, and Sn powder or In powder is Ag powder: 85.0 to 95.0 parts by mass, preferably 88.0 to 92.0 parts by mass, and more preferably 88.5 to 91.0 parts by mass; Cu powder: 5.0 to 13.0 parts by mass, preferably 6.0 to 12.0 parts by mass, and more preferably 7.0 to 11.0 parts by mass; Sn powder or In powder: 0.4 to 2.0 parts by mass, and preferably 0.5 to 1.5 parts by mass.
[0049] The method for mixing the brazing material raw materials is preferably to mix the metal powder, organic solvent, and binder, and mix them into a paste using a grinding machine, a planetary mixer, a three-roll mill, etc. Generally, organic solvents such as methyl cellosolve, ethyl cellosolve, isophorone, toluene, ethyl acetate, terpineol, diethylene glycol monobutyl ether, and texanol are used, while polymeric compounds such as polyisobutyl methacrylate, ethyl cellulose, methyl cellulose, and acrylic resins are used as binders.
[0050] Methods for applying the brazing paste to both sides of a ceramic substrate include the roll coater method, screen printing method, and transfer method, but screen printing method is preferred in order to apply the brazing paste evenly. In order to apply the brazing paste evenly using the screen printing method, it is preferable to control the viscosity of the brazing paste to 5 to 20 Pa·s. A brazing paste with excellent printability can be obtained by blending the organic solvent amount in the brazing paste in the range of 5 to 17 mass% and the binder amount in the range of 2 to 8 mass%.
[0051] In the joining step, the ceramic layer 1 and the brazing material layer 3 are joined via the brazing material. In this joining step, the laminate may be heated at a temperature increase rate of 20°C / min to 150°C / min in a nitrogen atmosphere, and then heated at a temperature of 750°C to 900°C.
[0052] The lower limit of the temperature rise rate is 20° C. / min or more, preferably 25° C. / min or more, and more preferably 30° C. / min or more. The temperature rise rate may be the average temperature rise rate from 20° C. to 750° C.
[0053] The peak temperature of the heating temperature in the bonding step may be 750° C. or higher, preferably 800° C. or higher, and more preferably 820° C. or higher.
[0054] A commonly known method for bonding ceramic circuit boards is to perform the bonding process in a vacuum atmosphere. However, in a vacuum atmosphere, rapid heating at a rate of 20° C. / min or more cannot be performed, and the temperature rise rate is usually 5° C. / min. In contrast, in this embodiment, nitrogen gas is selected from among inert gases as the heat medium, thereby enabling the above-mentioned rapid heating.
[0055] In the bonding step, the laminate may be heated and then cooled at a temperature decreasing rate of 10° C. / min to 100° C. / min. The lower limit of the cooling rate is, for example, 10° C. / min or more, preferably 13° C. / min or more, and more preferably 15° C. / min or more. The cooling rate may be the average cooling rate from 750° C. to 20° C.
[0056] The oxygen concentration of the nitrogen atmosphere in the bonding step is, for example, 500 ppm or less, preferably 200 ppm or less, and more preferably 120 ppm or less, which can ensure good connection of the ends of the ceramic-copper composite 100.
[0057] In the present embodiment, the heating in the bonding step may be, for example, a nitrogen heating furnace for heating a structure in which two or more flat laminates are stacked together. By using a nitrogen heating furnace, it becomes possible to appropriately control the conditions of the rapid heating, rapid cooling, and nitrogen atmosphere.
[0058] To form a circuit pattern on the copper layer 2 of the ceramic-copper composite 100, an etching resist may be applied to the copper layer 2 and then etched. There is no particular limitation on the etching resist, and for example, a commonly used ultraviolet-curing type or heat-curing type can be used. There is no particular limitation on the method of applying the etching resist, and for example, a known application method such as a screen printing method can be used.
[0059] The surface of the copper layer 2 on which the circuit pattern is formed may be subjected to electroless Ni plating, Au flash plating, displacement Ag plating, etc., as necessary. It is also possible to apply an anti-rust agent to the surface after smoothing it by grinding, physical polishing, chemical polishing, etc., without plating it.
[0060] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. Below, examples of reference forms are given. 1. A ceramic layer, a copper layer, and a brazing material layer interposed between the ceramic layer and the copper layer and containing Ag and Sn or In; A flat ceramic-copper composite comprising: A ceramic-copper composite, wherein, in at least one of the cut surfaces when the ceramic-copper composite is cut along a plane perpendicular to its main surface, a convexo-concave portion is formed on the copper layer side of the brazing material layer, and a plurality of Cu-rich phases are present in a state spaced apart from each other within at least one of the convex portions. 2. The ceramic-copper composite according to 1., A ceramic-copper composite, wherein at least one of the Cu-rich phases is configured in a streaky shape. 3. The ceramic-copper composite according to 2., The aspect ratio of the Cu-rich phase is greater than 1 and less than or equal to 10. 4. A ceramic-copper composite according to any one of 1. to 3., The number density of the Cu-rich phase is 0.1 / μm 2 More than 20 pieces / μm 2 Below is a ceramic-copper composite. 5. A ceramic-copper composite according to any one of 1. to 4., A ceramic-copper composite, wherein in an observation field of the cut surface, the ratio (L2 / L1) of the length L1 in the plate width direction of the observation field to the length L2 of the line segment at the interface between the brazing material layer and the copper layer is 1.25 or more and 5.0 or less. 6. A ceramic-copper composite according to any one of 1. to 5., The Cu-rich phase includes a fine phase having a size of 0.3 μm or more and less than 1.0 μm, and a coarse phase having a size of 1.0 μm or more and 7.5 μm or less. 7. A ceramic-copper composite according to any one of 1. to 6., A ceramic-copper composite, wherein the abundance ratio of Cu in the Cu-rich phase is 80 mass % or more. 8. A step of preparing a flat laminate in which a ceramic layer, a brazing material containing Ag, and a copper layer are laminated; A bonding step of heating the laminate at a temperature of 750° C. or more and 900° C. or less in a nitrogen atmosphere after increasing the temperature at a rate of 20° C. / min or more and 150° C. / min or less, The method for producing a flat ceramic-copper composite includes the ceramic layer, the copper layer, and a brazing material layer containing Ag and interposed between the ceramic layer and the copper layer. 9. A method for producing a ceramic-copper composite according to 8., comprising the steps of: The bonding step comprises heating the laminate and then cooling the laminate at a temperature decreasing rate of 10° C. / min or more and 100° C. / min or less. 10. A method for producing a ceramic-copper composite according to 8. or 9., comprising the steps of: The method for producing a ceramic-copper composite, wherein the oxygen concentration of the nitrogen atmosphere in the bonding step is 500 ppm or less. 11. A method for producing a ceramic-copper composite according to any one of 8. to 10., In the method for producing a ceramic-copper composite, the heating in the bonding step is performed by using a nitrogen heating furnace to heat a structure in which two or more of the flat plate-like laminates are stacked. EXAMPLES
[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0062] <Preparation of ceramic-copper composite> Example 1 Ag powder (Fukuda Metal Foil and Powder Co., Ltd.: Ag-HWQ, average particle size D50: 2.5 μm, specific surface area 0.4 m) was applied to both main surfaces of a silicon nitride substrate with a thickness of 0.32 mm. 2 / g) 89.5 parts by mass, Cu powder (manufactured by Fukuda Metal Foil & Powder Industry Co., Ltd.: Cu-HWQ) Average particle size D50: 3.0 μm Specific surface area 0.4 m 2 / g, ) 9.5 parts by mass, Sn powder (manufactured by Fukuda Metal Foil and Powder Industry Co., Ltd.: Sn-HPN, average particle diameter D50: 3 μm, specific surface area 0.1 m 2 For a total of 100 parts by mass of 1.0 part by mass of titanium hydride powder (TCH-100 manufactured by Toho Tech Co., Ltd.), an active metal brazing material containing 3.5 parts by mass of titanium hydride powder was applied at a coating amount of 8 mg / cm. 2 The coating was performed by screen printing. Thereafter, a metal plate for forming a circuit was placed on one side of the silicon nitride substrate, and a metal plate for forming a heat sink (both were C1020 oxygen-free copper plates with a thickness of 0.5 mm) was placed on the other side to obtain a laminate. Using a nitrogen heating furnace, the obtained laminate was heated from 25°C to 870°C at a heating rate of 90°C / min in a nitrogen atmosphere with an oxygen concentration of 100 ppm, and held at 870°C (bonding temperature) for 18 minutes (bonding time), and then cooled to 25°C at a heating rate of 15°C / min (bonding process). An etching resist was printed on the bonded copper plates, and the copper plates were etched with a ferric chloride solution to form a circuit pattern, resulting in a ceramic-copper composite.
[0063] (Examples 2 to 5) A ceramic-copper composite was obtained in the same manner as in Example 1, except that the joining step was changed to the joining conditions in Table 1.
[0064] (Comparative Examples 1 and 2) The joining process was carried out in a heating furnace at 1.0×10 -3 A ceramic-copper composite was obtained in the same manner as in Example 1, except that the joining conditions were changed to those in Table 1 in a vacuum of 0.1 Pa or less.
[0065] [Table 1]
[0066] The obtained ceramic-copper composite was evaluated based on the following evaluation items.
[0067] (SEM image observation) SEM images were obtained by observing the cut surfaces of the ceramic-copper composites of Examples 1 to 5 and Comparative Examples 1 and 2 with a scanning electron microscope. In the SEM images, black indicates the silicon nitride substrate, white indicates the brazing material layer, and gray indicates the copper plate.
[0068] In Table 1, Cu Ti phase structure 1 is an SEM image at 500x magnification, Cu Ti phase structure 2 is an SEM image at 2000x magnification, and Cu Ti phase structure 3 is an image obtained by binarizing the SEM image at 2000x magnification using the image analysis software GIMP2 (threshold value 90).
[0069] <Observation of Cu-rich phase in brazing layer structure> The Cu-rich phase in the brazing layer structure was evaluated by observing three fields of view, 40 μm long x 60 μm wide, near the center of the plate thickness cross section in the center of the longitudinal direction, at a magnification of 2000 times using a scanning electron microscope (JEOL JSM-6380) using backscattered electron images at any position on the joint interface of the cross section of the ceramic-copper composite. This method allows the observation of Cu-rich phases with a grain size of 0.1 μm or more. The observation magnification was set to 2000 times because if the observation magnification was too high, the field of view becomes narrow and a sufficient number of Cu-rich phases cannot be observed, and conversely, if the observation magnification was too low, Cu-rich phases less than 1 μm in size cannot be observed.
[0070] (tissue shape) By observing the images as described above, the presence or absence of irregularities in the brazing layer structure and the presence or absence of a Cu-rich phase in the protrusions were evaluated based on the following criteria. The average thickness of the brazing layer was calculated by measuring the thickness from the interface between the silicon nitride substrate and the brazing layer to the interface between the brazing layer and the copper plate, and averaging the maximum and minimum thicknesses. Measurements were performed in three visual fields, and the average of the three visual fields was used. In the region of the brazing material layer shown in the SEM image, if there is a portion that exceeds half the average thickness of the brazing material layer in the vertical direction from the interface between the silicon nitride substrate and the brazing material layer toward the copper plate side, it is determined that the brazing material layer has a convex portion, and if there is a portion that does not exceed half the average thickness of the brazing material layer, it is determined that the brazing material layer has a concave portion. Moreover, when the brazing material layer had a protrusion, the internal region of the protrusion was observed for a Cu-rich phase, and the presence or absence of the Cu-rich phase and the shape of the Cu-rich layer were evaluated.
[0071] (fine phase, coarse phase) The above image observation was used to check for the presence or absence of fine phases of 0.3 μm or more and less than 1.0 μm and coarse phases of 1.0 μm or more and 7.5 μm or less. The results are shown in Table 1. The abundance ratio of Cu in the Cu-rich phase was quantitatively analyzed using an electron beam excited X-ray analyzer (EPMA).
[0072] (L1, L2) By observing the above images, the length L1 of the observation field in the sheet width direction and the length L2 of the line segment at the interface between the brazing material layer and the copper layer were measured, and L1 / L2 was calculated. The results are shown in Table 1.
[0073] <Evaluation of Cu-rich phase in brazing layer structure> The SEM images obtained by the above-mentioned method were binarized using the image analysis software GIMP2 (threshold 90), and the images were analyzed to measure the aspect ratio and number density of the Cu-rich phase. The image processing software used for image analysis was Image-Pro Plus, manufactured by MediaCybernetics. The grain size of the Cu-rich phase in the brazing layer structure varies from 0.3 μm to several μm. The Cu-rich phase, which is a microphase with a grain size of 0.1 μm or more and less than 1.0 μm that can be observed with a scanning electron microscope, was analyzed for aspect ratio and number density. The average size of the Cu-rich phase was determined by observing three fields of view, measuring the centroid diameter of all the observed Cu-rich phases, and averaging the results. The number density of the Cu-rich phase was calculated by measuring the area of the brazing material layer structure using image analysis software Image-pro plus manufactured by Media Cybernetics, and calculating the number density of the Cu-rich phase by the following formula (I). Number density of Cu-rich phase (pieces / μm 2 ) = Number of Cu-rich phases / Area of brazing layer structure (I)
[0074] (Ag diffusion distance) The ceramic-copper composite was cut, embedded in resin, and the cross section was polished. Then, backscattered electron images were taken at three randomly selected fields of view (within a range of 250 μm in the horizontal direction of the joint interface) at a magnification of 500x using a scanning electron microscope, and the shortest distance (μm) between the silicon nitride substrate and the position of Ag in the copper plate that was closest to the copper plate surface was measured.
[0075] (Bond void ratio) The area of the joint voids in the ceramic-copper composite observed with an ultrasonic flaw detector (ES5000, Hitachi Power Solutions, Ltd.) was measured and divided by the area of the circuit pattern to calculate the joint void rate (area %).
[0076] (Heat cycle test) The ceramic-copper composite was subjected to 15 consecutive thermal cycles, each cycle consisting of 5 min at 350°C on a hot plate, 5 min at 25°C, 5 min at -78°C in a mixed solvent of ethanol and dry ice, and 5 min at 25°C. The copper plate, the brazing material layer and the nitride layer were then removed by etching, and the horizontal cracks that had occurred on the surface of the ceramic substrate were captured by a scanner at a resolution of 600 dpi x 600 dpi. The horizontal cracks were then binarized and calculated using the image analysis software GIMP2 (threshold 140), and the horizontal crack area was then divided by the circuit pattern area to calculate the crack rate (%) after the heat cycle.
[0077] The ceramic-copper composites of Examples 1 to 5 showed a lower crack rate after the heat cycle in the heat cycle test compared to Comparative Examples 1 and 2, and therefore showed excellent heat cycle characteristics.
[0078] This application claims priority based on Japanese Patent Application No. 2020-009305, filed on January 23, 2020, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0079] 1 Ceramic layer 2 Copper Layer 3 Brazing layer 4 Cu-rich phase 5 Ag-rich phase 6 Convex 100 Ceramic-copper composite
Claims
1. a ceramic layer, a copper layer, and a brazing material layer interposed between the ceramic layer and the copper layer and containing Ag and Sn or In; A flat ceramic-copper composite comprising: When the ceramic-copper composite is cut along a plane perpendicular to its main surface, at least one of the cut surfaces is Ag in the brazing material layer migrates into the copper layer, and an uneven portion is formed on the copper layer side of the brazing material layer, The convex portion of the uneven portion is a portion that exceeds a position of 1 / 2 of the average thickness of the brazing material layer from the interface between the ceramic layer and the brazing material layer toward the copper layer in a vertical direction, In at least one of the protrusions, a plurality of Cu-rich phases are present in a state separated from each other within a region surrounded by an Ag-rich phase, A plurality of the Cu-rich phases are configured in stripes and spaced apart from each other to form a stripe pattern, The abundance ratio of Cu in the Cu-rich phase present in the convex portion is 80 mass% or more, The abundance ratio of Ag in the Ag-rich phase present in the convex portion is 80 mass% or more. Ceramic-copper composite.
2. The ceramic-copper composite according to claim 1, The brazing material layer has a Cu-rich phase in an area other than the protrusions.
3. The ceramic-copper composite according to claim 1 or 2, A ceramic-copper composite, wherein a plurality of the Cu-rich phases are formed inside the convex portions constituted by the convex-shaped Ag-rich phase.
4. The ceramic-copper composite according to any one of claims 1 to 3, A ceramic-copper composite, wherein an Ag-rich phase is formed in at least a part of an outer edge of the protrusion that contacts the interface between the brazing material layer and the copper layer.
5. The ceramic-copper composite according to any one of claims 1 to 4, The brazing material layer has a brazing material layer structure in which an Ag-rich phase is continuous.
6. The ceramic-copper composite according to any one of claims 1 to 5, The aspect ratio of the streaky Cu-rich phase is greater than 1 and less than 10.
7. The ceramic-copper composite according to any one of claims 1 to 6, The number density of the Cu-rich phase is 0.1 / μm 2 More than 20 pieces / μm 2 The ceramic-copper composite is shown below.
8. The ceramic-copper composite according to any one of claims 1 to 7, In an observation field of the cut surface, a ratio (L2 / L1) of a length L1 in the plate width direction of the observation field to a length L2 of a line segment of an interface between the brazing material layer and the copper layer is 1.25 or more and 5.0 or less.
9. The ceramic-copper composite according to any one of claims 1 to 8, The Cu-rich phase includes a fine phase having a size of 0.3 μm or more and less than 1.0 μm, and a coarse phase having a size of 1.0 μm or more and 7.5 μm or less.
Citation Information
Patent Citations
Printed circuit board and evaluation and manufacture thereof
JP1998145039A
Ceramic circuit board and method for manufacturing the same
JP2005101415A
Bonded substrate and method for manufacturing bonded substrate
JP2018506496A
Ceramic circuit board, method for manufacturing ceramic circuit board, and module using ceramic circuit board
WO2018199060A1
Ceramic circuit board and production method therefor
WO2019022133A1